Hadith #2389 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A man said to Messenger of Allah (ﷺ): Messenger of Allah, I was overtaken by dawn while I was sexually defiled, and I want to keep fast. The Messenger of Allah (ﷺ) said: I am also overtaken by dawn while I am in the state of sexual defilement ; I also want to keep fast. I take a bath and I keep fast. The man said: Messenger of Allah, you are not like us ; Allah has forgiven you your past and future sins. The Messenger of Allah (ﷺ) became angry and said: I swear by Allah, I hope I shall be
Grade: Sahih

Hadith #2391 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
This was a special concession for him. If a man commits this act today, the expiation is necessary for him. Abu Dawud said: Al-Laith b. Sa’d, al-Awza’i, Mansur b. al-Mu’tamir and ‘Irak b. Malik have narrated this tradition like the one narrated by Ibn ‘Uyainah. Al-Awza’i narrated in his version the words: Beg pardon of Allah.
Grade: Sahih

Hadith #2428 - Sunan Abi Dawud - Abu Hurairah; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ja'far bin Iyas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
The father or Uncle of Mujibah al-Bahiliyyah visited the Messenger of Allah (ﷺ). He then went away and came to him (again) after one year when his condition and appearance had changed. He said: Messenger of Allah, do you not recognize me? He asked: Who are you? He replied: I am al-Bahili who came to you last year. He said: What has changed you? You were looking well, then you were good in appearance? He said: I have only food at night since I departed from you. Thereupon the Messenger of Allah
Grade: Da'if

Hadith #3246 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Prophet (ﷺ) said: One should not take a false oath at this pulpit of mine even on a green tooth-stick; otherwise he will make his abode in Hell, or Hell will be certain for him.
Grade: Sahih

Hadith #4166 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
A woman made a sign from behind a curtain to indicate that she had a letter for the Messenger of Allah (ﷺ). The Prophet (ﷺ) closed his hand, saying: I do not know this is a man’s or a woman’s hand. She said: No, a woman. He said: If you were a woman, you would make a difference to your nails, meaning with henna.
Grade: Hasan

Hadith #4254 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Unbasa bin Sa'id bin al-Aas عنبسة بن سعيد بن العاص بن سعيد; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The Prophet (ﷺ) said: The mill of Islam will go round till the year thirty-five, or thirty-six, or thirty-seven; then if they perish, they will have followed the path of those who perished before them, but if their religion is maintained, it will be maintained for seventy years. I asked: Does it mean seventy years which remain or seventy years which are gone by? He replied: It means (seventy years) that are gone by. Abu Dawud said: Those who recorded Khirash, the name of a narrator, are wrong.
Grade: Sahih

Hadith #4358 - Sunan Abi Dawud - Abdur Rahman Ibn 'Awf; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Amir al-Sha'bi عامر الشعبي; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Jarir bin 'Abdullah al-Bajli; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
Abdullah ibn AbuSarh used to write (the revelation) for the Messenger of Allah (ﷺ). Satan made him slip, and he joined the infidels. The Messenger of Allah (ﷺ) commanded to kill him on the day of Conquest (of Mecca). Uthman ibn Affan sought protection for him. The Messenger of Allah (ﷺ) gave him protection.
Grade: Hasan

Hadith #4694 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Uthman bin Ghyath عثمان بن غياث; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
We attended a funeral at Baql’ al-Gharqad which was also attended by the Messenger of Allah (May peace be upon him). The Messenger of Allah (May peace be upon him) came and sat down. He had a stick (in his hand) by which he began to scratch up the ground. He then raised his head and said : The place which every one of you and every soul of you will occupy in Hell or in Paradise has been recorded, and destined wicked or blesses. A man from among the people asked : Prophet of Allah! Should we no
Grade: Sahih

Hadith #4918 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ma'mar bin Rashid معمر بن راشد; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Nasr bin 'Ali bin Nasr bin 'Ali; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umm Kulthum bint 'Uqba (Sunan Abi Dawud)
The Prophet (ﷺ) said: The believer is the believer’s mirror, and the believer is the believer’s brother who guards him against loss and protects him when he is absent.
Grade: Hasan

Hadith #4919 - Sunan Abi Dawud - Abd al-Whab bin Aby عبد الوهاب بن أبي بكر; Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; al-Rabi' bin Sulaiman bin Da'ud الربيع بن سليمان بن داود; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Nafi' bin Yazid al-Kula'i نافع بن يزيد الكلاعي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
The Prophet (ﷺ) said: Shall I not inform you of something more excellent in degree than fasting, prayer and almsgiving (sadaqah)? The people replied: Yes, Prophet of Allah! He said: It is putting things right between people, spoiling them is the shaver (destructive).
Grade: Sahih

Hadith #5139 - Sunan Abi Dawud - Aabad bin Musa al-Khtly عباد بن موسى الختلي; Abdullah bin 'Amr bin al-'Aas; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن (Sunan Abi Dawud)
I said: Messenger of Allah! to whom should I show kindness? He replied: Your mother, next your mother, next your mother, and then comes your father, and then your relatives in order of relationship. The Messenger of Allah (ﷺ) said: If a man asks his slave whom he freed for giving him property which is surplus with him and he refuses to give it to him, the surplus property which he refused to give will be called on the Day of resurrection as a large bald snake. Abu Dawud said: Aqra’ means a s
Grade: Hasan Sahih